A GEOPHYSICAL PROSPECTING USING INDUCED POLARIZATION METHOD ON GOLD-BEARING SULFIDE DEPOSITS AT PASAWAHAN AREA, SIMPENAN SUB-DISTRICT, SUKABUMI DISTRICT, WEST JAVA - Maman Surahman (Indonesian Mining Journal, 2014)
Induced polarization (IP) is a geophysical imaging technique used to identify sulfidized sedimentary rocks in the form of quartz veins in Pasawahan, Sukabumi District,West Java. The voltage is then monitored through two other electrodes. The sulfide is a lense shape with resistivity of 1 – 10 W and induced polarization of 130 – 150 m sec. It is included in a 300,000-ton quartz vein.